Respuestas

  • Usuario de Brainly
2013-05-27T01:11:59+02:00
X + 3/4 = 2/7
x = 2/7 - 3/4
x = 8/28 - 21/28
x = - 13/28

x - (-5/7) = 11/2
x + 5/7 = 11/2
x = 11/2 - 5/7
x = 77/14 - 10/14
x = 67/14

x + 3/11 = 3/8
x = 3/8 - 3/11
x = 33/88 - 24/88
x =  9/88

x - 4/9 = 16/5
x = 16/5 + 4/9
x = 144/45 + 24/45
x = 168/45

x + 9/4 - 3/4 = 12/7
x = 12/7 + 3/4 - 9/4
x = 12/7 - 6/4
x = 3/14

espero que te sirva, salu2!!!

2013-05-27T01:12:46+02:00
X + 3/4 = 2/7
x = 2/7 - 3/4 
x = 8/28 - 21/28
x = - 13/28

x - (-5/7) = 11/2
x + 5/7 = 11/2
x = 11/2 - 5/7 
x = 77/14 - 10/14
x = 67/14

x + 3/11 = 3/8 
x = 3/8 - 3/11
x = 33/88 - 24/88
x =  9/88

x - 4/9 = 16/5
x = 16/5 + 4/9
x = 144/45 + 24/45
x = 168/45